Estratégias de leitura na compreensão de artigos de opinião - Levi Rosa de Campos (2019)
This work is a teaching proposal aimed at the development of reading skills ocused on opinion piece genre. Its starting point are the Portuguese teaching guidelines from the National Curriculum Parameters (Parâmetros Curriculares Nacionais) (PCN,1998), from Minas Gerais Common Core Standards (Conteúdo Básico Comum do Estado de Minas Gerais) (CBC,2006) and from the National Curriculum Standards (Base Nacional Comum Curricular) (BNCC, 2017), which, as long as reading is concerned, regulate that pedagogical activities should promote reading skills development and should also enable students to comprehend social practices through language use and reflection. According to these documents, reading cannot be seen as a mere word decoding, as it implies an interaction from which the reader actively conveys the given message through both linguistic and extralinguistic elements. Besides the reading concepts from the official documents, this work also brings some reflections on the work at schools with argumentative genres and on reading practices from the textbook. From these considerations, a pedagogic intervention was concocted and conducted with a middle school ninth grade group from Colégio Tiradentes da Polícia Militar - Gameleira, based on the didactic sequence by Dolz e Schneuwly et al. (2004). First, a reading activity was proposed in order to diagnose the subjects solidified reading skills, this activity helped elaborating and conducting the following activities; finally, as a final production, the subjects produced a short video presenting their understanding and evaluation of na opinion piece previously read. Through a process evaluation, it was possible to realize that this work activities helped the students better understand the communicative goal of an opinion piece and its basic characteristics. The students could also practice argumentation and empathy development by respectfully listening to their peers opinions.